Expectations of i-Tree Eco as a tool for urban tree management in Nordic cities - Sjöman, Johanna Deak; Tuhkanen, Eeva-Maria; Mänttäri, Miia; Cimburová, Žofie; Stålhammar, Sanna; Barton, David N.; Randrup, Thomas B. (Frontiers in Sustainable Cities, 2024)
While urban forests are recognized as imperative toward climate adaptation in cities and provide health and recreational benefits to citizens, municipal tree officers often struggle to find successful governance arrangements and budget support toward long-lasting investment and implementation in new planting schemes and protection of existing trees. Since its release in 2006, i-Tree Eco has helped urban tree officers worldwide to find tangible leverage in the means of quantitative mapping, numeric measures, and economic values of ecosystem services. This may in turn help ease gridlocks and potentially support constructive dialogues across sectors, with decision-makers and public engagement. With the release of i-Tree Eco v. 6 in Europe 2018, 13 Nordic cities were engaged in a larger research project with ambitions to use i-Tree Eco for the purpose of retrieving numeric and monetary data of the biophysical structures and ecosystem services of the urban forest. Based on questionnaires and semi-structured interviews, we present the results from the Nordic i-Tree project with a focus on expectations, opportunities, and potential barriers experienced in using i-Tree Eco in urban forest management. The most prominent expectation and foreseeing opportunities were recognized toward using numeric information on trees to change policies and support cross-sectoral collaboration while reaching politicians and the public. Identified barriers involved how limited resources are spent on public outreach and how information about the project to relevant stakeholders were not distributed from the beginning which may have implications on the dissemination of results. As some important ecosystem services, e.g., cultural services, are not captured by i-Tree Eco, presenting the partial value of urban trees may pose also potential risks to cross-sectoral collaboration. Other findings conclude that although numeric information on ecosystem services is seen as beneficial in terms of communicating with different stakeholders, a deeper understanding toward the criteria used in the valuation process and the potential risks of numeric approaches may provide more context-specific applications.